2011
DOI: 10.1007/s00044-011-9841-8
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic effects of novel pentabromobenzylisothioureas in human leukemia cell lines

Abstract: A series of new pentabromobenzylisothioureas [ZKK-1–ZKK-5; (ZKKs)] carrying additional substituents on nitrogen atoms has been synthesized. The ZKKs were found to induce apoptosis in HL-60 (human promyleocytic leukemia) and K-562 (human chronic erythromyeloblastoid leukemia) cell lines in a concentration-dependent manner at low micromolar concentrations. ZKK-3 [(N,N′-dimethyl-S-2,3,4,5,6-pentabromobenzyl)isothiouronium bromide] showed the highest proapoptotic activity in HL-60 cells, whereas ZKK-2 [N-methyl-S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Several substituted isothiourea derivatives were reported to possess significant cardiovascular properties as nitric oxide synthase inhibitors [1][2][3][4][5], and calcium channel blockers [6]. Isothiourea derivatives were also reported to display potent antimicrobial [7,8], anticancer [9,10], and anti-anthelmintic [11] activities. The incorporation of the highly lipophilic adamantyl group positively modulates the therapeutic index of several compounds through various mechanisms [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Several substituted isothiourea derivatives were reported to possess significant cardiovascular properties as nitric oxide synthase inhibitors [1][2][3][4][5], and calcium channel blockers [6]. Isothiourea derivatives were also reported to display potent antimicrobial [7,8], anticancer [9,10], and anti-anthelmintic [11] activities. The incorporation of the highly lipophilic adamantyl group positively modulates the therapeutic index of several compounds through various mechanisms [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Tested chemicals. ZKKs were synthesized in a reaction of pentabromobenzylobromide with N-substituted thioureas, according to previously described procedures (20). Five ZKK derivatives were used in this study: ZKK-1, ZKK-2, ZKK-3, ZKK-13 and TRIM, as well as BEN.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that low micromolar concentrations of novel ZKKs (ZKK-1 to ZKK-5) induced concentration-dependent, proapoptotic effects on HL-60 and K-562 human leukaemia cell lines (21). These effects may be related to CK2 inhibition because CK2 is known to suppress apoptosis.…”
Section: Western Blot Analysis Of Cell Death Regulator B-cell Lymphommentioning
confidence: 99%
See 2 more Smart Citations